2002
DOI: 10.1007/s00468-002-0163-9
|View full text |Cite
|
Sign up to set email alerts
|

Variation of pigment composition and antioxidative systems along the canopy light gradient in a mixed beech/oak forest: a comparative study on deciduous tree species differing in shade tolerance

Abstract: The acclimation of leaf pigments and antioxidative systems along the vertical canopy light gradient was determined in mature European beech (Fagus sylvatica L.) and sessile oak [Quercus petraea (Matt.) Liebl.] trees in a mixed beech/oak forest in northwest Germany. The aim of the study was to investigate if the higher shade tolerance of beech, relative to oak, is correlated with characteristics of the leaf pigment composition and antioxidative systems. Both species showed a similar acclimative response to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
43
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 53 publications
9
43
2
4
Order By: Relevance
“…7), while in shade leaves such reversion was shown to be extremely slow (Barth et al 2001). The level of the antioxidant AsA in tree leaves has been reported to increase with the average PAR received in the canopy (Hansen et al 2002). In the present study, shade leaves of all four species tested responded to changes in light conditions with respect to their pools of AsA + DHA (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…7), while in shade leaves such reversion was shown to be extremely slow (Barth et al 2001). The level of the antioxidant AsA in tree leaves has been reported to increase with the average PAR received in the canopy (Hansen et al 2002). In the present study, shade leaves of all four species tested responded to changes in light conditions with respect to their pools of AsA + DHA (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Changes in chlorophyll a to b ratio can also reflect multiple adjustments in response to light quality and quantity. Ratio of two photosystems (PSI and PSII) as well as the size of light-harvesting antenna complexes modify chlorophyll a to b ratio (Hansen et al 2002;Kitajima and Hogan 2003;Fan et al 2007;Niinemets 2010a). Apart from changes in incident light availability, there is also important light gradient within the leaf, associated both with changes in carotenoid to chlorophyll ratio and chlorophyll a to b ratio (Terashima and Hikosaka 1995 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that excess light enhances the production of ROS and subsequently POD activity in chloroplasts (Hansen et al 2002;Gill, Tuteja 2010).…”
mentioning
confidence: 99%
“…ROS cause damage to proteins, lipids, DNA, and carbohydrates. They also control many processes like plant growth, programmed cell death, abiotic stress responses, and pathogen defence by influencing the expression of a number of genes (Hansen et al 2002;Gill, Tuteja 2010). Unfavourable conditions such as excess light (Hansen et al 2002), drought, and salt stress (Wang et al 2007) enhance the production of ROS in chloroplasts.…”
mentioning
confidence: 99%
See 1 more Smart Citation